2009
DOI: 10.1007/s10682-009-9299-z
|View full text |Cite
|
Sign up to set email alerts
|

Idle slow as you grow old: longitudinal age-related metabolic decline in a wild passerine

Abstract: Physiological changes due to aging are intensively studied as they have farreaching implications for the mechanistic and evolutionary theories of senescence. In this respect, metabolic rate has been suggested to play a role for the deterioration and damage of cells and tissues with age, partly due to the generation of reactive oxygen species. To mitigate such damage, individuals can be predicted to reduce basal metabolic rate (BMR) with age. This prediction has been verified in humans and some laboratory anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…Even though other studies have shown that age can affect metabolic rates (Roberts and Rosenberg 2006;Broggi et al 2009;Moe et al 2009), the short time span in this study suggests that the effect here merely is a side effect of other factors, such as differences in molt progress. Molt can affect metabolic measurements in birds (see, e.g., Klaassen 1995;Cyr et al 2008), and since zebra finches constantly replace worn feathers, it is possible that birds of different ages also display slightly different molt progress.…”
Section: Discussioncontrasting
confidence: 71%
“…Even though other studies have shown that age can affect metabolic rates (Roberts and Rosenberg 2006;Broggi et al 2009;Moe et al 2009), the short time span in this study suggests that the effect here merely is a side effect of other factors, such as differences in molt progress. Molt can affect metabolic measurements in birds (see, e.g., Klaassen 1995;Cyr et al 2008), and since zebra finches constantly replace worn feathers, it is possible that birds of different ages also display slightly different molt progress.…”
Section: Discussioncontrasting
confidence: 71%
“…This is interesting because aging does not appear to have a uniform effect on RMR across different study systems. Metabolic senescence has been described in humans (Manini 2010); in laboratory organisms, such as rats (Even et al 2001) and zebra finches (Moe et al 2009); and in some wild animals (Broggi et al 2010). However, several studies have not found effects of aging on metabolic rate.…”
Section: Aging and Metabolic Ratementioning
confidence: 99%
“…Metabolic senescence has been described in humans (Roberts and Rosenberg, 2006) and laboratory animals such as rats (Even et al, 2001), but its occurrence is not necessarily widespread, especially in the wild. Longitudinal studies on relatively long-lived vertebrates are rare and although some studies have detected metabolic senescence (Broggi et al, 2010), others have found no signs of it (Moe et al, 2007). The few studies that have looked into insect metabolic senescence have produced mixed results.…”
Section: Repeated Measurements Of Resting and Flight Metabolic Ratesmentioning
confidence: 99%